2011
DOI: 10.1091/mbc.e10-11-0923
|View full text |Cite
|
Sign up to set email alerts
|

Akt-phosphorylated PIKE-A inhibits UNC5B-induced apoptosis in cancer cell lines in a p53-dependent manner

Abstract: UNC5B induces apoptosis in the absence of its cognate ligand netrins and acts as a tumor suppressor. UNC5B is a direct transcriptional target of p53 upon UV stimulation. Here we show that Akt phosphorylates PIKE-A and regulates its association with UNC5B and inhibits UNC5B-provoked apoptosis in a p53-dependent manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 29 publications
2
34
1
Order By: Relevance
“…PIKE-A is a downstream effector of various hormones, including prolactin, insulin, and netrin-1 (22,24,40,41). In this report, we further demonstrate that PIKE-A is a new player in TNF-α signaling to control muscular energy metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…PIKE-A is a downstream effector of various hormones, including prolactin, insulin, and netrin-1 (22,24,40,41). In this report, we further demonstrate that PIKE-A is a new player in TNF-α signaling to control muscular energy metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…In the presence of netrin-1, the multimerized receptors recruit different adapter proteins and activate PI3K/Akt, ERK1/2, and small GTPase RhoA/Rac-1/Cdc-42 to affect cell survival, motility, invasion, and morphogenesis through cytoskeletal rearrangements (22)(23)(24). It is reported that PP1A acts downstream of RhoA in LPA-induced YAP dephosphoryaltion (25) and PI3K and ERK1/2 signaling is involved in the regulation of PP1A activity in cancer cells (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…It has also demonstrated that PIKE-A associates with UNC5B in glioblastoma cell lines 39 . The PIKE-A/UNC5B binding is tightly regulated by Akt, in which Akt-induced phosphorylation of PIKE-A on Ser-472 promotes its interaction with UNC5B.…”
Section: Functions Of Pike In Tumorigenesismentioning
confidence: 97%
“…As such, netrin-1 might stimulate Akt activation, which subsequently phosphorylates PIKE-A, escalating its binding to UNC5B, and thereby inhibiting the receptor cleavage and apoptosis-inducing activity. In addition, PIKE-A (S472) phosphorylation feed backs positively to further elevate the Akt activity and leads to p53 degradation through the Akt-MDM2 pathway, resulting in down-regulation of UNC5B 39 . Since PIKE-L associates with DCC in the brain, conceivably, other PIKE isoforms may interact with DCC and demonstrate a potential function in tumorigenesis.…”
Section: Functions Of Pike In Tumorigenesismentioning
confidence: 99%